Plastid senescence - Thomas, Howard (Henry Stewart Talks, 2007)
Critical role of senescence in plant growth, development, survival and adaptation, The senescing chloroplast (gerontoplast) as a phase of plastid differentiation, New biochemistry and gene expression in the chloroplast-to-gerontoplast transition, Reversibility, manipulation and exploitation of plastid senescence, Evolutionary origins of plastid senescence